ANALISIS SPASIAL ASPEK KESEHATAN LINGKUNGAN DENGAN KEJADIAN FILARIASIS DI KOTA PEKALONGAN (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2017)
Pekalongan City is one of the endemic cities of filariasis with mf-rate > 1 %. One of many factors that can influence filariasis is environmental factor. The aim of this research was to figure out the spatial imaging of environmental health such as shrub existence, puddle, wastewater pipeline, and livestock existence with filariasis in Pekalongan City. The study was quantitative descriptive with descriptive survey. Data were analyzed with spatial analysis using GIS in 6 filariasis-endemic subdistricts, i.e. Banyurip Ageng, Jenggot, Bandengan, Pabean, Kuripan Lor, dan Kertoharjo. The study showed that filariasis transmission was in the area with shrub and wastewater pipeline existence. Risk factor of wastewater pipeline existence was in all research places. Risk factor of livestock existence was in 3 subdistricts of Bandengan, Kertoharjo, dan Jenggot. Rice fields existence was a environmental risk factor in Kertoharjo and Banyurip Ageng.